The UN Sustainable Development Goals; using WHO ‘Health Promoting Schools' to create change. - Macnab, Andrew John; Mukisa, Ronald (GHMJ (Global Health Management Journal), 2017)
Accepted: 23 May 2017. Published: 22 June 2017. Abstract is not required for photo essay. Below are the summary and keywords the journal provides for insight to our reader.  Summary: The article highlights the global epidemiological significance of the United Nations Sustainable Development Goals (SDGs), particularly in addressing poverty. It proposes an innovative approach using the World Health Organization's (WHO) Health Promoting School (HPS) model to address factors affecting children's health and well-being. The HPS approach focuses on multi-disciplinary strategies within school communities, aiming to generate lifelong awareness and positive behaviors that influence the social determinants of health. School-based programs, especially in low and middle-income countries, often include activities like planting school gardens, contributing to improved nutrition, academic achievement, and skill development. The article emphasizes the relevance of these initiatives to specific SDGs (1-6) and underscores the role of schools in reaching a large population to address social determinants of health. Keywords: Sustainable Development Goals (SDGs) World Health Organization (WHO) Health Promoting School (HPS) model Multi-disciplinary strategies School-based health promotion Social determinants of health School gardens Nutrition Academic achievement Skill development Low and middle-income countries Micronutrients Food security Sustainable agriculture.